Therapeutic effect of increased openness: Investigating mechanism of action in MDMA-assisted psychotherapy. (August 2017) - Wagner, Mark T; Mithoefer, Michael C; Mithoefer, Ann T; MacAulay, Rebecca K; Jerome, Lisa; Yazar-Klosinski, Berra; Doblin, Rick
A growing body of research suggests that traumatic events lead to persisting personality change characterized by increased neuroticism. Relevantly, enduring improvements in Post-Traumatic Stress Disorder (PTSD) symptoms have been found in response to 3, 4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy. There is evidence that lasting changes in the personality feature of "openness" occur in response to hallucinogens, and that this may potentially act as a therapeutic mechanism of change. The present study investigated whether heightened Openness and decreased Neuroticism served as a mechanism of change within a randomized trial of MDMA-assisted psychotherapy for chronic, treatment-resistant PTSD. The Clinician-Administered PTSD Scale (CAPS) Global Scores and NEO PI-R Personality Inventory (NEO) Openness and Neuroticism Scales served as outcome measures. Results indicated that changes in Openness but not Neuroticism played a moderating role in the relationship between reduced PTSD symptoms and MDMA treatment. Following MDMA-assisted psychotherapy, increased Openness and decreased Neuroticism when comparing baseline personality traits with long-term follow-up traits also were found. These preliminary findings suggest that the effect of MDMA-assisted psychotherapy extends beyond specific PTSD symptomatology and fundamentally alters personality structure, resulting in long-term persisting personality change. Results are discussed in terms of possible mechanisms of psychotherapeutic change.